Canopy ants on the briefly deciduous tree (Elateriospermum tapos Blume) in a tropical rainforest, southern Thailand - Sunthorn Sotthibandhu; Suparoek Wattanasit; Sopark Jantarit (Songklanakarin Journal of Science and Technology (SJST), 2009)
A year-round investigation of the ant species present in the canopies of the briefly deciduous tree, Elateriospermum tapos Blume was conducted in the tropical rainforest at Khao Nan National Park (KNNP), Nakhon Si Thammarat Province, Southern Thailand during May 2006-March 2007. Three permanent plots of 50x50 m2 were established 500 m apart. In each plot a single plant was randomly selected for fogging at bimonthly intervals. A total of 3,285 individual ants were identified and belonged to 5 subfamilies 31 genera and 123 morphospecies. Ants in the subfamily Myrmicinae were the most dominant species followed by Formicinae, Dolichoderinae, Pseudomyrmicinae and Ponerinae, respectively. In terms of abundanceand number of species, the top four genera were Crematogaster, Camponotus, Polyrhachis and Pheidole, whereasCamponotus(Karavaievia) sp.2, Technomyrmex sp.1, Oecophylla smaragdina (Fabricius),Crematogaster(Crematogaster) sp.7, and Camponotus (Karavaievia)cf. dolichoderoides were dominant in the numbers of individuals. When E. tapos species shed their leaves briefly around February-March, the species richness of canopy ants (P>0.05) did not significantly change. Explanations for this finding are discussed.